Seismic performance of end-plate connections between T-shaped CFST columns and RC beams. (June 2018) - Peng, Zhong; Dai, Shao-Bin; Pi, Yong-Lin; Zhang, Yi-Chao; Huang, Jun
Abstract: An innovative end-plate connection is proposed by welding an H-shaped steel corbel to the end-plate and the end-plate is connected to the special T-shape concrete-filled steel tubular (CFST) column using a number of high-strength bolts. This paper presents experimental and numerical studies on the seismic performance of the new end-plate connection between T-shaped CFST columns and reinforced concrete (RC) beams with slabs. Tests of seven specimens are conducted: a specimen is tested under the monotonic loading in order to obtain the load-displacement curve and the development of strains until the failure; and six specimens are tested under cyclic loading. The seismic behaviour of the connections in terms of strength, ductility, energy dissipation, strength degradation and stiffness degradation are evaluated. The experimental results demonstrate that the proposed connections exhibit good seismic performance and that the length of the H-shaped steel corbel and the diameter of the high-strength bolt played important roles in improving the seismic behaviour of the connections. A finite element (FE) model based on ABAQUS is developed and validated by the experimental results for the numerical investigation of the seismic behaviour of the proposed end-plate connections. It has been found that the reinforcement ratio of beam and the concrete strength of the beam and slab can affect the seismic performance of the specimens, but the effect of the axial compressive force ratio of the column on the seismic performance can be neglected. Highlights: An innovative end-plate connection between T-shaped CFST column and RC beam with slab is proposed. Conduct monotonic and cyclic tests on seven specimens. Seismic performance of the connection is excellent. The validated finite element model is used to carry out extensive parametric study.